Laser cleaning of the archaeological metal sample from the Danube - Suzana Polić; Bore Jegdić; Suzana Linić; Vesna Bikić; Miloš Pavlović (Zaštita Materijala)
The paper presents the results of laser cleaning of corrosive and other deposits on a metal archaeological artefact from the Danube. Nd: YAG laser, energy up to 750 mJ and wavelengths λ = 1064 nm and 532 nm is used. The cleaning efficiency was examined in the function of laser energy, wavelength, and number of pulses, i.e. the time of exposure and moist of the surface of the sample. The results of removal of unwanted layers from the surface of the artefact and morphological changes on the base material were examined by optical and scanning electronic microscopy (OM and SEM). Micro-chemical changes have been determined by energy dispersive X-ray analysis (EDX) and x-ray fluorescence spectrometry (XRF). It has been shown that λ = 532 nm has higher efficiency for cleaning this sample and that the surface moisture has very small influence on laser cleaning efficiency. Research carried out on the archaeological object from the Danube shows that the application of lasers in the cleaning of undesirable layers is very efficient, safe and environmentally friendly.